Leadership styles in Kosovo businesses: - Rexhepi, Aziz; Hysen Sogojeva; Besarta Rexhepi; Bislim Lekiqi (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
It has often been said that the style of decision making is reflective of leadership style. Numerous studies in the field of management and leadership show that decision making style is a key factor contributing to the success of managers and organizational performance. In Kosovo, decision-making styles are conditioned by many factors. It should be noted that the most important factor in adequately matching the characteristics and knowledge of workers and the specifics required at work lies in the high number of unemployment. This often causes the workforce to perform work for which there is no professional training in the field. Also, from the research we found that there is a difference in the decision making style and the adaptation of the characteristics of work and employees between sectors. In general, the public sector tends to have more security for employees in the workplace, which drives them to look for other jobs, but the private sector shows more willingness to take risks. The difference also lies in the nature and activity of the work between the sectors studied. Often there are different approaches of employees and leaders between the banking sector or design organizations. Our study, which is based on empirical data, will present facts on decision-making styles, and factors that influence the determination or adaptation / non-adaptation of employees to the jobs in the sectors studied. Keywords: style, decision making, intuitive, alert, manager.